Clinical characteristics and treatment outcomes of isolated myeloid sarcoma without bone marrow involvement: a single-institution experience - Lee, Jung Yeon; Chung, Haerim; Cho, Hyunsoo; Jang, Ji Eun; Kim, Yundeok; Kim, Soo-Jeong; Kim, Jin Seok; Hyun, Shin Young; Min, Yoo Hong; Cheong, June-Won (Blood research, 2017)
Isolated myeloid sarcoma (MS) is a rare extramedullary tumor mass composed of malignant myeloid precursor cells without any evidence of leukemia in the peripheral blood and bone marrow. We describe the clinical characteristics and outcomes of patients diagnosed with isolated MS at our institution. We retrospectively reviewed 9 of 497 acute myeloid leukemia (AML) patients (1.8%) with isolated MS. Isolated MS patients were divided into 2 groups according to the first-line treatment strategy: systemic treatment only (S) or local treatment with or without systemic treatment (LS). The most common site of MS occurrence was the head and neck area (N=4, 44.4%), followed by the anterior mediastinum (N=2, 22.2%) and the gastrointestinal tract (N=2, 22.2%). The tumors of 4 patients (44.4%) eventually evolved to AML, in a median time of 13.4 months (range, 2.4-20.1 mo). The number of patients achieving complete remission after first-line treatment was higher in the LS group (N=5, 83.3%) than in the S group (N=1, 33.3%) ( =0.226). All patients in the LS group survived, but those in the S group died ( =0.012). Accurate and rapid diagnosis using various modalities and the early initiation of intensive combined treatment may be the optimal strategies to reduce the risk of isolated MS subsequently evolving to AML. To fully understand the characteristics of isolated MS, a larger number of patients from a multinational study is necessary.